2022
DOI: 10.1186/s12888-022-04355-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the connection between parental bonding and smartphone addiction in Chinese medical students

Abstract: Background Smartphone addiction bodes adverse consequences, affecting different populations, including medical students. Parental bonding in childhood had been associated with addiction and recovery in later life. Therefore, this study aimed to examine the associations between parental bonding and smartphone addiction among Chinese medical students. Method Binary logistic regressions were used to investigate the associations between parental bondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Conversely, our approach only requires capturing beef images using a smartphone and uploading them to the model deployed on the cloud platform. With smartphone subscriptions reaching 6.5 billion in 2022 and projected to reach 7.7 billion in 2023 (Xin et al., 2022), using smartphones can provide a convenient method for sample collection without the need for trained personnel. Therefore, the smartphone‐based approach using computer vision for hydrocolloid detection could provide a simple way for meat quality testing in developing countries and resource‐limited environments.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, our approach only requires capturing beef images using a smartphone and uploading them to the model deployed on the cloud platform. With smartphone subscriptions reaching 6.5 billion in 2022 and projected to reach 7.7 billion in 2023 (Xin et al., 2022), using smartphones can provide a convenient method for sample collection without the need for trained personnel. Therefore, the smartphone‐based approach using computer vision for hydrocolloid detection could provide a simple way for meat quality testing in developing countries and resource‐limited environments.…”
Section: Resultsmentioning
confidence: 99%
“…Smartphone addiction is considered a behavioral addiction and refers to an excessive use of smartphones that interferes with users’ daily life and has harmful effects[ 11 ]. Evidence from China indicated that the prevalence of smartphone addiction among college students ranges from 20% to 50%[ 12 - 14 ]. Notably, smartphone addiction is associated with mental health problems[ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current global prevalence of IA among adolescents is 8.8% [7] and 11.3% among Chinese adolescents [8]. Studies have shown that IA may cause a range of serious problems in adolescents, including attention disorders [9], academic performance decline [10], interpersonal relationship problems [11,12], family dysfunction [13], anxiety [14], and depression [15]. IA has seriously harmed adolescents' physical and mental health.…”
Section: Introductionmentioning
confidence: 99%